The improbable theory of Ana & Zak - Katcher, Brian (2015)
Ana is an honor student obsessed with being successful at everything academic, Clayton is her thirteen-year-old genius brother, the youngest student in their high school and Zak is gamer who is forced to join the quiz team by his teacher--but when Clayton sneaks off to a science fiction convention in Seattle while they are all there for a quiz bowl tournament, Ana is forced to rely on the unreliable Zak to find him.
Accelerated Reader AR
Keywords: Contests -- Juvenile fiction; Science fiction -- Congresses -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; High school student activities -- Juvenile fiction; Academic achievement -- Juvenile fiction; Genius -- Fiction; High schools -- Fiction; Schools -- Fiction; Tacoma (Wash.) -- Juvenile fiction; Seattle (Wash.) -- Juvenile fiction; Young adult fiction